Estudio de una mutación en papaya (Carica papaya L.) que produce letalidad de plantas femeninas. - Mora-Newcomer, Eric; Bogantes-Arias, Antonio (Agronomía Mesoamericana, 2005)
Study of a mutation in papaya (Carica papaya L.) leading to female lethality. During the 1995-2003 period a new mutation in papaya was discovered and studied. Papaya is a polygamous species and presents the three possible sex forms: female, male, and hermaphrodite. Male and hermaphrodite plants are obliged heterozygotes and their alleles are dominant over the female allele. Female plants are recessive homozygotes. The three homozygous dominants are lethal combinations. Therefore, a self-pollinated hermaphroditic plant segregates in a 2:1 manner, whereas the cross between female and hermaphrodite plants leads to a 1:1 segregation. In this work, we report a mutation in a genetic line that leads to a diminished percentage of female plants (5% females vs. 95% hermaphrodites), which suggests the appearance of lethality to the female allele in its homozygous condition. The cross between a female and hermaphrodite plant of this line leads to a 2:1 segregation instead of the expected 1:1. These results also suggest that the few female plants of this line arise from the reversion of the lethality of one of these female alleles, leading to a viable heterozygote. This line also presents some anomalies to the hermaphrodite flowers at low frequencies. It is suggested that all of these anomalies are probably epigenetic in nature, possibly caused by a transposon.